Variances in family carers' quality of life based on selected relationship and caregiving indicators: A quantitative secondary analysis. (10th November 2016) - Naef, Rahel; Hediger, Hannele; Imhof, Lorenz; Mahrer‐Imhof, Romy
Abstract : Aims and objectives: To determine subgroups of family carers based on family relational and caregiving variables and to explore group differences in relation to selected carer outcomes. Background: Family caregiving in later life holds a myriad of positive and negative outcomes for family members' well‐being. However, factors that constitute family carers' experience and explain variances are less well understood. Design: A secondary data analysis using cross‐sectional data from a controlled randomised trial with community‐dwelling people 80 years or older and their families. Methods: A total of 277 paired data sets of older persons and their family carers were included into the analysis. Data were collected via mailed questionnaires and a geriatric nursing assessment. A two‐step cluster analysis was performed to determine subgroups. To discern group differences, appropriate tests for differences with Bonferroni correction were used. Results: Two family carer groups were identified. The low‐intensity caregiver group (57% of carers) reported high relationship quality and self‐perceived ease of caregiving. In contrast, the high‐intensity caregiver group (43% of carers) experienced significantly lower relationship quality, felt less prepared and appraised caregiving as more difficult, time intensive and burdensome. The latter cared for older, frailer and more dependent octogenarians and had significantly lower levels of quality of life and self‐perceived health compared to the low‐intensity caregiver group. Conclusions: A combination of family relational and caregiving variables differentiates those at risk for adverse outcomes. Family carers of frailer older people tend to experience higher strain, lower relationship quality and ability to work together as a family. Implications for practice: Nurses should explicitly assess family carer needs, in particular when older persons are frail. Family carer support interventions should address caregiving preparedness, demand and burden, as well as concerns situated in the relationship.